UPAYA PENYELESAIAN SENGKETA WILAYAH DAN PENGAMANAN KAWASAN PERBATASAN MARITIM ANTARA REPUBLIK INDONESIA DAN REPUBLIK DEMOKRATIK TIMOR LESTE - Noval Ardhan Djadi; Oktafyano Rudolfo Haryanto; Yohanes Arman (JOURNAL OF LAW AND NATION, 2023)
A country is recognized by having a firm and clear area or territory, the existence of a government that controls the country, and the existence of people or residents who inhabit the area and are recognized by neighboring countries that border and are accepted internationally. The border area of a country is the main capital of a country's sovereignty. Border areas often cause various problems related to regional management. There are three main problems in the management of border areas between countries, namely: Determination of boundary lines both on land and sea, Security of border areas, Development of border areas. In the border between the Republic of Indonesia and the Democratic Republic of Timor Leste, there is a border problem, namely land grabbing. The Government of the Republic of Indonesia said the issue of State boundaries is a matter of State sovereignty so that it cannot be underestimated, therefore our vigilance must be increased in order to maintain the territorial integrity of the Republic of Indonesia. Border management is not only in terms of security but must also be considered the prosperity of border areas. The purpose of this scientific paper is to determine efforts to resolve border area disputes between the Republic of Indonesia and the Democratic Republic of Timor Leste and to determine the management of maritime border area security between the Republic of Indonesia and the Democratic Republic of Timor Leste. In an effort to resolve the territorial boundary dispute, it can be seen that the dispute settlement method carried out by both parties, in this case Indonesia and Timor Leste, is to use peaceful dispute settlement, by negotiation or negotiation, the two countries negotiate and review several cooperation agreements that have been carried out. Preventive measures against real threats, unreal threats, and threat mindset on the maritime border between Indonesia and Timor Leste by carrying out Intelligence Operations in the Field of Investigation, optimizing regional or regional intelligence functions, synergy in the regions, increasing security patrols and counterintelligence by carrying out positive activities including Social Communication Development and Regional Defense Development activities to the community and students in maritime border area between Indonesia and Timor Leste.